Трав’янистий покрив рівнинно-пейзажного району дендропарку “Тростянець” - Nesterenko, V.P.; Ilyenko, A.A.; Medvedev, V.A. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2007)
As well as the phytocenotical and taxonomic characteristics of the grass cover of typical part flat region of dendropark Trostyanets. The ways of improving park's grass of glades and groups of trees are outlined.